Trends in Problematic Infection of Lesions: Etiology and Multidrug Resistance - Ranjit, Srijana; Maskey, Sunima; Shrestha, Ruchi (Journal of Nepalgunj Medical College, 2025)
Introduction: Infection of wound and pus lead to delayed healing, prolonged hospital stay, increased healthcare costs and rising mortality and morbidity. Their clinical impact is increased by emerging multidrug resistance, particularly among common pathogens in hospital settings. Understanding local bacteriological trends and antimicrobial susceptibility is crucial for guiding effective treatment. Aims: To determine the trends in bacteriological pathogens of infected lesions, assess antimicrobial susceptibility patterns, and evaluate the prevalence and distribution of Multidrug Resistant organisms among patients presenting with wound or pus infections. Methods: A retrospective descriptive study was conducted at Dhulikhel Hospital from September 2022 to September 2025. All wound and pus samples submitted for culture and sensitivity testing were included. Standard microbiological methods were used for bacterial isolation, identification, and antimicrobial susceptibility testing following Clinical and Laboratory Standard Institute guidelines. Data were analyzed to determine species distribution, sensitivity patterns, and Multidrug Resistance prevalence across age groups. Results: Of 8,199 samples processed, 2,678 (32.7%) showed bacterial growth. Gram-positive organisms were slightly predominant (55.5%). Staphylococcus aureus (33.79%) was the most common pathogen showing high susceptibility to cloxacillin (97.2%) and amoxicillin-clavulanic acid (85.5%), while Methicillin Resistant Staphylococcus aureus isolates remained sensitive to linezolid (90.7%) and vancomycin (79.2%). Among gram-negative bacteria, Escherichia coli displayed high sensitivity to gentamicin (84.8%) but low susceptibility to β-lactams and carbapenems. Acinetobacter spp. demonstrated extensive Multidrug Resistance with poor response to most antibiotic classes. Overall Multidrug resistance prevalence was 51.6%, highest among elderly patients (83.3%), followed by adults (54.2%) and children (36.7%). Conclusion: The study highlights Staphylococcus aureus and Enterobacterales as major pathogens in wound infections and reveals a concerning rise in Multidrug Resistance, especially among gram-negative bacilli. These findings emphasize the need for strengthened antimicrobial stewardship, continuous surveillance, and evidence-based empirical therapy